Fully secure hierarchical inner product encryption for privacy preserving keyword searching in cloud. (2018) - Zhang, Leyou; Wang, Zhuanning; Mu, Yi; Hu, Yupu
Cloud computing provides dynamically scalable resources provisioned as a service over networks. But untrustworthy cloud service provider (CSP) offers a big obstacle for the adoption of the cloud service since CSP can access data in cloud without data owner's permission. Hierarchical inner product encryption (HIPE) covers all applications of anonymous encryption, fully private communication and search on encrypted data, which provide trusted data access control policy to CSP. However, the existing works only achieve either selectively attribute-hiding or adaptively attribute-hiding under some strong assumptions in the public key setting. These schemes only support limited class of functions and can not protect the privacy of the query. To overcome these shortcomings, a novel HIPE in private key setting is issued. The proposed scheme achieves both fully secure and security reduction under the decisional linear (DLIN) assumption in the standard model. It has longer-size secret keys and size ciphertexts and brings the high computational complexity. Therefore, a variant of the basic scheme is presented with the same security but shorter ciphertexts.